LARYNGEAL PARAGANGLIOMA: A CASE REPORT - Lê, Văn Khảng; Vũ , Đăng Lưu; Nguyễn , Thị Ngọc; Nguyễn , Thị Thu Hằng (Tạp chí Điện quang & Y học hạt nhân Việt Nam, 2024)
Paragangliomas correspond to tumors of neuroendocrine origin of chromaffin and non-chromaffin in the paraganglia of the sympathetic or parasympathetic nervous system. Laryngeal and thyroid paragangliomas that arise from the laryngeal paraganglia are extremely rare. Diagnosing two kinds of paragangliomas preoperatively is challenging due to non-specific cytology, pathology, and imaging features, and overlaps with many other neoplasms. Complications in surgery of laryngeal and thyroid paragangliomas may be associated with significant intraoperative bleeding and excision with adherence to nearby structures, including the recurrent laryngeal nerve.